A celebration of the work of Richard Cook, MD: A pioneer in understanding accidents, safety, human factors, and resilience. Issue 1 (March 2023) - O'Connor, Michael F.; Woods, David; Perry, Shawna J.; Patterson, Emily S.; Nunnally, Mark E.; Nemeth, Christopher; Fairbanks, Rollin J. (Terry); Donchin, Yoel; Bitan, Yuval
Dr. Richard Cook was a physician, educator, scholar, and researcher. He was a brilliant thinker and writer. Richard's CV lists 41 peer reviewed publications, 39 conference proceedings, 6 technical reports, 30 books/book chapters that were cited about 10, 000 times (as of September 2022). Richard has excelled in multiple careers and was remarkably giving of his time, devoting 100s of thousands of hours of his life presenting, debating, corresponding, mentoring, and challenging the world, in formal and informal settings, to mature toward more complex, realistic thinking about the world as a sociotechnical entity. Our community recognizes him mainly for his key role in the start and expansion of the patient safety movement. This paper presents quintessence from a panel session that honors Richard's work. The 7 panelists and moderator present Richard's legacy, introduce varied aspects of his work, and consider how we can take his legacy forward to cope with future challenges. It is a moment to step back, remind ourselves of patient safety's evolution from the 90's until today, the power of resilience for the future of healthcare complex systems, and how to build momentum that can succeed at scale.